1998
DOI: 10.1111/j.1444-0938.1998.tb06744.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the corneal endothelium in vertebrates

Abstract: INTRODUCTION: In vertebrates, a corneal endothelium is essential for the maintenance of corneal transparency in a variety of environments, including aerial, terrestrial and aquatic. Knowledge of the surface structure of the corneal endothelium may assist our understanding of this unique tissue and its evolutionary development. Except for humans and some mammals, there have been few studies of other vertebrates, particularly the unique Australian species. METHODS: The field emission scanning electron microscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
54
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 28 publications
13
54
1
5
Order By: Relevance
“…The high cost of specular microscopes and the difficulty in obtaining good images in injured endothelial areas are common challenges or barriers to the use of this technique (ANDREW et al, 2001;PIGATTO et al, 2005a;SAAD et al, 2008). SEM has been widely used to compare the endothelial ultrastructure of vertebrates and to evaluate the effects of medications, chemicals, or surgical procedures on the endothelium (COLLIN & COLLIN, 1998;PIGATTO et al, 2004;PIGATTO et al, 2005a;PIGATTO et al, 2005b;PIGATTO et al, 2009). Changes in endothelial cell dimensions can occur as a result of processing the cornea for SEM and the data obtained with regard to endothelial cell density cannot be compared with those obtained using specular microscopy (SCHUTTEN & VAN HORN , 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The high cost of specular microscopes and the difficulty in obtaining good images in injured endothelial areas are common challenges or barriers to the use of this technique (ANDREW et al, 2001;PIGATTO et al, 2005a;SAAD et al, 2008). SEM has been widely used to compare the endothelial ultrastructure of vertebrates and to evaluate the effects of medications, chemicals, or surgical procedures on the endothelium (COLLIN & COLLIN, 1998;PIGATTO et al, 2004;PIGATTO et al, 2005a;PIGATTO et al, 2005b;PIGATTO et al, 2009). Changes in endothelial cell dimensions can occur as a result of processing the cornea for SEM and the data obtained with regard to endothelial cell density cannot be compared with those obtained using specular microscopy (SCHUTTEN & VAN HORN , 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Humans and rabbits have twenty to thirty microvilli in the cell superficies, and these structures react to tox- ic substances changing their sizes (Collin & Collin 1998). Both the endothelium control and experimental groups presented almost the same morphological characters in scanning electron microscopy analyses, and the microvillus and interdigitation were evident in all sample images.…”
Section: Discussionmentioning
confidence: 70%
“…The results observed in this study show that normal swine corneal endothelium consisted of a continuous monolayer with mainly hexagonal cells, but were also found cells with five sides and with seven sides. Previous studies conducted involving vertebrate animals have shown that there is predominance of cells with hexagonal shape and, in lower proportion, there is presence of five-and seven-sided cells (Collin & Collin, 1998, Pigatto et al 2005, Gum et al 2007, Tamayo-Arango et al 2009, Bercht et al 2015, Coyo, et al 2015.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations